Analysis of regional economic metabolism through modeling. (February 2020) - Silva, Afonso; Augusto, Bruno; Rafael, Sandra; Reis, Johnny; Lopes, Myriam; Costa, Sérgio; Borrego, Carlos
Abstract: A linear economic model has proven to lead society into an unsustainable situation. Current policies have been promoting the transition for a circular economy across Europe. Portugal's Action Plan for Circular Economy foresees the development of regional agendas, which include the characterization of regional economic metabolism. Taking resources inputs, extractions and imports into account, as well as the generated outputs, such as exports and emissions to the environment are a fundamental need for an efficient resources management. Indicators associated with regional economic metabolism allow the identification of inefficient use of natural resources and energy, and opportunities for circularity, which can promote new business models and investments. In this context and to fulfill the current need of evaluating the regional economic metabolism, this work describes the development of the REMET-UA (REgional METabolism) model. This model was developed to take into account the specificities of Portuguese regions, allowing an analysis with a high-resolution level.